2019
DOI: 10.21608/asnj.2019.69571
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nursing Psychological Support and Teaching Physiotherapy Guideline on Improving Pain Level for Patients with Temporomandibular Joint Disorders

Abstract: Stress and temporomandibular joint (TMJ) are often linked to each other. The symptoms of stress manifest in physical ways, often leading to a TMJ disorders and can cause jaw tension or pain. Physiotherapy treatment is very effective in relieving and managing temporomandibular joint disorders (TMJDs), even when the symptoms are long-standing and severe. Aim: To evaluate the effect of nursing psychological support and teaching physiotherapy guideline on improving pain level for patients with TMJDs. Research desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is seen that exercise and conservative physiotherapy management are frequently used in TMJ disorders [5][6][7][8][9][10][11][12][13]. Long-term yoga practices have been shown to affect the pain center in the brain and improve pain tolerance [7].Therefore, it has been suggested that yoga could be used in chronic pain management [2,5,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is seen that exercise and conservative physiotherapy management are frequently used in TMJ disorders [5][6][7][8][9][10][11][12][13]. Long-term yoga practices have been shown to affect the pain center in the brain and improve pain tolerance [7].Therefore, it has been suggested that yoga could be used in chronic pain management [2,5,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is recommended that posture and awareness exercises should be performed to correct the head and neck posture. It has been reported that methods such as hypnosis, meditation and yoga may be useful in the treatment of myofacial pain of TMD [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%